Improving Indonesia Financial Literacy through Financial Education - Firdausi Sulaksana, Ratu Dintha Insyani Zukhruf (Business Education Program of Universitas Pendidikan Indonesia, 2022)
The purpose of this research is to find out more about how to improve Indonesia's financial literacy through financial education programs. The method used in this research is descriptive research with literature study research techniques. The results of this study suggest that every financially literate individual, company and government is required to be increasingly responsible for financial planning, investing and spending their resources. Education on the financial side can be given not only in formal terms such as in high school and college classes, but can also be given in the work environment, family, finance courses to the government. So that they can answer the demands of the development of industry 4.0 and society 5.0, also become financially literate individuals and take an active role in economic activities and be able to manage family finances